Treatment of post-partum depression: a review of clinical, psychological and pharmacological options - Elizabeth Fitelson; Sarah Kim; Allison Scott Baker; et al (Dove Medical Press, 2010)
Elizabeth Fitelson1, Sarah Kim4, Allison Scott Baker3, Kristin Leight21Director, 2Attending Psychiatrist, TheWomen's Program, 3Child and Adolescent Psychiatry Fellow, Division of Child Psychiatry, 4PGY-I Resident in Psychiatry, Department of Psychiatry, Columbia University Medical Center, New York, NY, USAAbstract: Postpartum depression (PPD) is a common complication of childbearing, and has increasingly been identified as a major public health problem. Untreated maternal depression has multiple potential negative effects on maternal-infant attachment and child development. Screening for depression in the perinatal period is feasible in multiple primary care or obstetric settings, and can help identify depressed mothers earlier. However, there are multiple barriers to appropriate treatment, including concerns about medication effects in breastfeeding infants. This article reviews the literature and recommendations for the treatment of postpartum depression, with a focus on the range of pharmacological, psychotherapeutic, and other non-pharmacologic interventions. Keywords: postpartum depression, postnatal depression, lactation, antidepressant, hormone therapy, psychotherapy, bright light therapy, omega-3